Identity in Changing Context: Factors of losing Identity in new developed part of the city of Famagusta, North Cyprus - Hourakhsh Ahmad Nia; Yousif Hussien Suleiman (Alanya Hamdullah Emin Paşa Üniversitesi, 2017)
Historical cities due to its magnificent building in its context have a tremendous influence on the formation of city identity, which is created through the interaction of natural, social and built elements. Unfortunately, modernization after the industrial revolution couldn’t adapt itself to the vernacular area, owing to the fact that cities began to lose their identity and sense of belonging to the environment. The new technology of construction lets the cities to expand itself outside, but in this transformation, some factors which have an influence on the identity of the city have been forgotten. In this research, it is aimed to analysis Physical and social factors which are causing the loss of identity in the city of Famagusta (Gazimagusa). Both qualitative and qualitative methods have been used in this research and the adopted techniques are personal observation, sketches, and comparing new development part of the city with the traditional part. The research will try to answer the question of why urban sprawl could not maintain the identity of the city of Gazimagusa?. This research revealed that Globalization by neglecting historical housing principles is the main factor which threatening the identity of the city.